Factors Influencing Project Delay: A Case Study of the Vale Malaysia Minerals Project (VMMP) - Mohd Nawi, Mohd Nasrun; Deraman, R; Hasmori, M.F; Hasmori, M.A Azimi,; Lee, A. (International Journal of Supply Chain Management, 2016)
Delays are one of the biggest problems faced by the construction industry. The delays in construction projects have significant financial and social impact to parties involved in the projects. The main objective of this study is to explore the causes of delay in the Vale Malaysia Minerals Project (VMMP) in Lumut, Perak. This study was conducted by using a qualitative approach. A series of  face to face interviews were conducted with an expert from construction organization and  VMMP staff.  Responses were analysed qualitatively using content analysis  and a comprehensive interpretation was developed. The results revealed that several factors that contribute to the delay in VMMP completion, i.e. communication, delayed in material delivery, and poor management on site, etc. Time and cost overrun were the common effects of delays in construction project. The findings of this study will help the project manager or the client to take necessary measures and to use of supply chain management  to avoid delays of project completion in a construction project.